2008
DOI: 10.1111/j.1750-3841.2008.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Total Reflectance–Fourier Transform Infrared Spectroscopy Coupled with Multivariate Analysis for Measurement of Acesulfame‐K in Diet Foods

Abstract: Fourier transform infrared (FTIR) spectroscopy was investigated as a method for analysis of acesulfame-K content after a simple extraction procedure for certain commercial diet food samples. Partial least squares (PLS) models were developed for prediction of acesulfame-K using select spectral ranges on the basis of relevant IR absorption bands associated with acesulfame-K. The acesulfame-K content of test food samples was predicted accurately in the fingerprint region between 1100 and 1300 cm(-1) with a maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The use of Fourier transform infrared (FTIR) spectroscopy and multivariate analysis has advantages over other techniques and provides a rapid, robust, inexpensive qualitative analytical method to assess the qualities of various food samples. For examples, some researchers have applied FTIR spectroscopy to detect inverted sugar adulteration in honey (Sivakesava and Irudayaraj 2000; Sivakesava and Irudayaraj 2001b; Lichtenberg‐Kraag and others 2002; Daniel‐Kelly and others 2004; Ruoff and others 2006), sugars, and artificial sweeteners in dairy products (Shim and others 2008; Khurana and others 2008a, 2008b); others used the same technique to determine adulteration of fruit purees, milk, and oils (Tay and others 2002; Irudayaraj and others 2003; Ozen and others 2003; Khurana and others 2008a, 2008b; Vardin and others 2008). Tewari and Irudayaraj (2004) and Bertelli and others (2007) have applied FTIR to quantify sugar in honeys and to classify various honey regions; however, their honey collection was geographically limited and little detailed implementation for spectral data has been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Fourier transform infrared (FTIR) spectroscopy and multivariate analysis has advantages over other techniques and provides a rapid, robust, inexpensive qualitative analytical method to assess the qualities of various food samples. For examples, some researchers have applied FTIR spectroscopy to detect inverted sugar adulteration in honey (Sivakesava and Irudayaraj 2000; Sivakesava and Irudayaraj 2001b; Lichtenberg‐Kraag and others 2002; Daniel‐Kelly and others 2004; Ruoff and others 2006), sugars, and artificial sweeteners in dairy products (Shim and others 2008; Khurana and others 2008a, 2008b); others used the same technique to determine adulteration of fruit purees, milk, and oils (Tay and others 2002; Irudayaraj and others 2003; Ozen and others 2003; Khurana and others 2008a, 2008b; Vardin and others 2008). Tewari and Irudayaraj (2004) and Bertelli and others (2007) have applied FTIR to quantify sugar in honeys and to classify various honey regions; however, their honey collection was geographically limited and little detailed implementation for spectral data has been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In soap formulation, FTIR spectroscopy has also been used to determine the water content [1]. Recent studies have shown that FTIR spectroscopyattenuated total reflectance (ATR) combined with chemometrics is a simple, non-invasive, and reliable method necessitating minimum labor and chemicals for quantitative analysis [5]. One of the chemometric techniques frequently used for analysis of fats and oils and their products such as soap is multivariate calibration, as it facilitates the rapid and concurrent determination of each component in the complex mixtures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Carrez I and II solutions (reagents used to precipitate proteins and fats) were prea a pared and added to the foods under slightly heated conditions for sample clarifi cation [7,26]. Th fi is is followed by centrifugation to separate proteins Th and fatty material from the water-soluble supernatant in complex matrices such as ice-cream, chocolate syrup and coffee creamers [27]. Th ff ff e superTh natant can then be filtered and diluted in preparation for instrumental fi analysis.…”
Section: Lim Et Al Modifi Ed the Lle And Sle Procedures Developed Bymentioning
confidence: 99%